Refining technologies for the purification of crude biodiesel - Atadashi, I.M.; Aroua, Mohamed Kheireddine; Abdul Raman, Abdul Aziz; Sulaiman, N.M.N. (2011)
In biodiesel production, downstream purification is an important step in the overall process. This article is a critical review of the most recent research findings pertaining to biodiesel refining technologies. Both conventional refining technologies and the most recent biodiesel membrane refining technology are reviewed. The results obtained through membrane purification showed some promise in term of biodiesel yield and quality. Also, membranes presented low water consumption and less wastewater discharges. Therefore, exploration and exploitation of membrane technology to purify crude biodiesel is necessary. Furthermore, the success of membrane technology in the purification of crude biodiesel could serve as a boost to both researchers and industries in an effort to achieve high purity and quality biodiesel fuel capable of replacing non-renewable fossil fuel, for wide range of applications. (C) 2011 Elsevier Ltd. All rights reserved.